Panel Discussion 3 | Open access emphasis in Australia - WHITEHEAD, Derek (Institutional Knowledge at Singapore Management University, 2021)
The panelist covered the open access landscape in Australia, including developments in open access repositories in Australasia, Creative Commons in Australia and New Zealand, developments in open data, with an emphasis on open education resources in Australian universities.